Suitability of selected legumnious plant for development of maruca testulalis larvae. - Jackai, L.E.N.; Singh, S.R. (1983)
Flowers of eight plant species were evaluated under laboratory conditions for their suitability as larval growth media for the cowpea pod borer, Maruca testulalis. The plants tested were Crotalaria retusa, C. juncea, C. saltiana, C. misereniensis, C. amazonas, Cajanus cajan and the principal host of the borer, Vigna unguiculata (cowpea), was included for comparison. Based on the data obtained on larval mortality and growth indices (GI) the plants were divided into 3 categories namely: I: Those causing 0–30% mortality and having GI value ≥ 60% form suitable host plants. This group only included V. unguiculata. — II: Those plant species causing 30 ≤ 50% larval mortality and having GI value 30% ≤ 60% of the principal host plant (Cajanus cajan, Crotalaria amazonas, C. saltiana, C. mucronata). This group of species is marginally suitable as hosts. — III: Plants causing 50–100% larval mortality and having GI value ≤ 30% of principal host plant (C. retusa, C. juncea and C. misereniensis). Previously published data on the oviposition preference of the adult moth are discussed in the light of the present findings and the use of C. juncea as a possible trap crop.